Evaluating different methods of potential GDP estimates: The case of Mexico - Corona, Francisco; Orraca, Pedro; López-Pérez, Jesús (Estudios Económicos de El Colegio de México, 2022)
With the purpose of contributing to the literature that focuses on the estimation of Potential Gross Domestic Product (GDP), this study evaluates four different estimation methods of Potential GDP using quarterly data from Mexico for the period 1998:Q1-2020:Q2. The procedures used for its estimation are: 1) Heuristic methods, 2) The Hodrick Prescott filter, 3) Non-Stationary Dynamic Factor Model, and 4) The Permanent-Transient (PT) decomposition of Gonzalo and Granger (1995). We conclude that, econometrically, the best results are obtained when using the PT decomposition.